Melatonin protects against epirubicin-induced cardiotoxicity - ERCAN, FERİHA (ELSEVIER GMBH, 2007)
We investigated the cytoprotective effect of melatonin in epirubicin-induced cardiotoxicity using four experimental groups of mate Wistar rats: untreated control rats, epirubicin-treated rats, epirubicin+melatonin-treated rats, and melatonin-treated rats. We examined the histopathological. and biochemical, effects of melatonin on the epirubicin-induced changes and measured the Levels of the lipid peroxication end-product (malondialdehyde, MDA), an indicator of nitric oxide (NO) synthesis (nitrite/nitrate production), and reduced glutathione (GSH) in the heart. We also studied the extracellular matrix components (fibronectin, laminin) in the heart. Vacuole formation, mitochondrial. deformation and degeneration, and disordered myofibrillary structures were detected ultrastructurally in the epirubicin-treated group. The degeneration was reduced in the heart tissues of the epirubicin+melatonin group. Epirubicin increased the nitrite/nitrate production, but did not change the MDA and GSH levels significantly. Melatonin treatment Lowered the nitrite/nitrate concentrations, while increasing the GSH levels, which exceeded the Levels in epirubicin+melatonin-treated rats. We conclude that the epirubicin increased the nitrozative stress, not the oxidative stress, in heart tissue, and the cardioprotective effect of melatonin was partially attributed to the suppression of epirubicin-induced nitrozative stress. These results suggest that melatonin partially protects against epirubicin-induced cardiotoxicity. (C) 2006 Elsevier GmbH. All rights reserved.
Keywords: epirubicin; cardiotoxicity; nitrite/nitrate production; histopathology; melatonin; NITRIC-OXIDE; DOXORUBICIN CARDIOMYOPATHY; LIPID-PEROXIDATION; TOXICITY; INJURY; EXPRESSION; EFFICACY; THERAPY; HORMONE; OXYGEN